ENHANCING STUDENTS’ SPEAKING SKILL USING PODCAST: AN EXPERIMENTAL STUDY - Edy Kristianto Pabebang (Graduate Program, University of Islam Malang, 2021)
Given the fact that learning nowadays mainly employs the use of technology, many studies have attempted to document the effectiveness of the technology on language learning achievement. To continue the scholarship, the present study was designed to investigate EFL learners’ speaking achievement after learning using podcast. Data were collected through interviews and Liker’s scale questionnaire. The result of the data found was analysed by using SPSS Application. The results of the research showed that the students’ speaking performance after giving treatment was significantly improved. It was proved by the data of the students’ mean score post-test was higher than in pre-test (55.60 > 77.30). It indicates that the use of podcast can empower students in speaking skill. The analysis indicated that the significant value was higher than p-value (0.05>0.000), it means that the alternative hypothesis was accepted. Moreover, the students stated interested in learning speaking toward podcast. It was proved by the mean score of students’ interests was 55.40 and considered as moderately interested.